I love Lucy. The third season [videorecording (DVD)] - Ball, Lucille, 1911-1989; Arnaz, Desi, 1917-1986; Frawley, William, 1887-1966; Vance, Vivian; Ernie Ford, Tennessee, 1919-1991; Asher, William, 1921-2012; Daniels, Marc; Kern, James V., 1909-1966; Oppenheimer, Jess; Oppenheimer, Jess; Davis, Madelyn Pugh; Carroll, Bob, Jr., 1918-2007 (CBS Broadcasting Inc., 2015)
Cuban-born bandleader Ricky Ricardo and his wife, Lucy, live in a Brownstone apartment building on East 68th Street in New York City. The beautiful, but daffy Lucy has the nasty habit of getting into jams, scrapes, and predicaments of all kinds. Their best friends and landlords, Fred and Ethel Mertz, frequently find themselves in the middle of Lucy's outlandish escapades. Now in the third season of Lucy's hilarious adventures; the Ricardos adjust to being parents, but will Lucy's motherhood affect her show biz ambitions?